STABILITAS DINAMIS BETON ASPAL CAMPURAN PANAS DIBAWAH VARIASI TEMPERATUR - Eva Azhra Latifa; Nuzul Barkah Prihutomo; Mulyono Mulyono (Politeknik Negeri Jakarta, 2013)
ABSTRACT This research is part of a long-term study in an effort to discover a kind of asphalt concrete mix that is both economical and highly durable at up to 600 celsius under flood water submersion. The research is conducted by testing the dynamic stability of hot mix asphalt concrete as to simulate vehicle wheel load on a flexible road pavement. The tested mix utilizes portland cement and stone dust as the filler aggregate, as well as soft-gradation stone ash bina marga 2010 with pertamina asphalt, asphalt concrete mix with retona asphalt, and asphalt concrete mix with superpave-gradation aggregate. All those mixes undergo the marshall stability test as well as residual stability and refusal density tests beforehand to achieve the most optimum composition. The marshall stability test is conducted with different submersion times, ranging from 24, 72 to 120 hours, at temperatures ranging from 300, 380 to 600 celsius. The dynamic stability of the mixes is tested by a wheel-tracking device at 300 and 600 celsius. The data is analyzed through the regression analysis method. After treatment, results showed that the mix of bina marga fine gradation with stone dust filler and retona asphalt 55has highest dynamic stability with lowest rate of deformation. Keyword : filler aggregate, superpave gradation, bina marga fine gradation, marshall characteristic, dynamic stability